Strength and Drying Shrinkage of Alkali-Activated Slag Paste and Mortar - Mao-chieh Chi; Jiang-jhy Chang; Ran Huang (Advances in Civil Engineering)
The aim of this study is to investigate the strengths and drying shrinkage of alkali-activated slag paste and mortar. Compressive strength, tensile strength, and drying shrinkage of alkali-activated slag paste and mortar were measured with various liquid/slag ratios, sand/slag ratios, curing ages, and curing temperatures. Experimental results show that the higher compressive strength and tensile strength have been observed in the higher curing temperature. At the age of 56 days, AAS mortars show higher compressive strength than Portland cement mortars and AAS mortars with liquid/slag ratio of 0.54 have the highest tensile strength in all AAS mortars. In addition, AAS pastes of the drying shrinkage are higher than AAS mortars. Meanwhile, higher drying shrinkage was observed in AAS mortars than that observed comparable Portland cement mortars.